Uptake of tire-derived compounds in leafy vegetables and implications for human dietary exposure - Sherman, Anya; Hämmerle, Luzian Elijah; Ben Mordechay, Evyatar; Chefetz, Benny; Hüffer, Thorsten; Hofmann, Thilo (Frontiers in Environmental Science, 2024)
Introduction: Tire and road wear particles are one of the most abundant types of microplastic entering the environment. The toxicity of tire and road wear particles has been linked to their organic additives and associated transformation products. Tire and road wear particles, and associated tire-derived compounds are introduced to the agricultural environment via atmospheric deposition, irrigation with reclaimed wastewater, and the use of biosolids (treated sewage sludge) as fertilizer. In the agricultural environment, these tire-derived compounds could be taken up by edible plants, leading to human exposure.Methods: Sixteen tire-derived compounds were measured in twenty-eight commercial leafy vegetable samples from four countries. Based on the results, the estimated daily intake of these tire-derived compounds was calculated due to leafy vegetable consumption based on local diets under a mean and maximum concentration scenario.In commercial leafy vegetables, six tire-derived compounds were detected: benzothiazole (maximum concentration -238 ng/g dry weight), 2-hydroxybenzothiazole (maximum concentration -665 ng/g dry weight), DPG 1,3-diphenylguanidine (maximum concentration -2.1 ng/g dry weight), N-(1,3-dimethylbutyl)-N′-phenyl-p-phenylenediamine 6PPD (6PPD, maximum concentration -0.4 ng/g dry weight), IPPD N-Isopropyl-N-phenyl-4phenylenediamine (IPPD, maximum concentration -0.1 ng/g dry weight), and CPPD N-phenyl-N-cyclohexyl-p-phenylenediamine (CPPD, maximum concentration -0.3 ng/g dry weight). At least one compound was present in 71% of samples analyzed. The estimated daily intake for DPG 1,3-diphenylguanidine ranged from 0.05 ng/person/day in the mean scenario to 4.0 ng/person/day in the maximum scenario; benzothiazole ranged from 12 to 1296 ng/person/day; 6PPD ranged from 0.06 to 2.6 ng/person/day; IPPD ranged from 0.04 to 1.1 ng/person/day; CPPD ranged from 0.05 to 2.6 ng/person/day. Discussion: Statistical analyses did not reveal correlation between known growth conditions and tire-derived compound concentrations in the leafy vegetable samples. The estimated daily intake via leafy vegetable consumption was generally lower than or comparable to the estimated daily intake via other known sources. However, we show that tire-derived compounds are taken up by foodstuff, and exposure might be higher for other produce. Future studies are needed to uncover pathways of tire-derived compounds from road to food, assess the exposure to transformation products, and investigate the biological effects associated with this exposure.